“Perspectivas da metodologia qualitativa em pesquisas na área de educação” - de Almeida, Fernando José; Romanowski, Joana Paulin; do Carmo Dahle de Almeida, Siderly; Buzzi Rausch, Rita; Vercellino, Soledad (REVISTA INTERSABERES, 2022)
.